2013
DOI: 10.1002/pd.4042
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant right subclavian artery in Down syndrome fetuses

Abstract: In our study, the ARSA in combination with other ultrasound signs increased the risk for trisomy 21 by factor of 45, but the independent ability of ARSA as an isolated marker to predict fetal Trisomy 21 is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 15 publications
(42 reference statements)
4
56
0
Order By: Relevance
“…Several authors recommended karyotyping even if ARSA is the only positive marker [5,11], while it has been claimed that ARSA without another sonographic finding is not a powerful enough argument to recommend karyotyping [12]. In three previous series there was no case of trisomy 21 with isolated ARSA [4,6,12]. On the contrary, Chaoui et al [2] reported 5 cases of trisomy 21 having ARSA, and in 1 (20%) of them ARSA was the only positive sonographic marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors recommended karyotyping even if ARSA is the only positive marker [5,11], while it has been claimed that ARSA without another sonographic finding is not a powerful enough argument to recommend karyotyping [12]. In three previous series there was no case of trisomy 21 with isolated ARSA [4,6,12]. On the contrary, Chaoui et al [2] reported 5 cases of trisomy 21 having ARSA, and in 1 (20%) of them ARSA was the only positive sonographic marker.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether ARSA can be used as an isolated marker of Down syndrome, or only in combination with cardiac or extracardiac sonographic findings is yet to be established. Some of the previous studies showed the presence of trisomy 21 in cases with isolated ARSA [2,9,10,11], while in the other studies ARSA was associated with another sonographic finding in all cases with a chromosomal anomaly [4,6,12]. Moreover, the estimated likelihood ratio of isolated ARSA for Down syndrome was reported as 3.94 in a meta-analysis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An abnormal origin of the right subclavian artery (SCA) in subjects with a left aortic arch is an uncommon malformation in the general population (0.4-2%) [1,2,3] and occurs in 8-37.5% of subjects in high-risk populations [3,4,5]. The right SCA normally arises from the right brachiocephalic trunk.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight the relevance of the anatomy of the subclavian arteries, especially in cases of an aberrant right subclavian artery, where this vessel is absent in view IX. Interest in an aberrant right subclavian artery has increased, owing to its association with trisomy 21 and cardiac defects, 10,12,[35][36][37][38][39] although this association seems less marked when the condition is isolated. 16 Other authors have also reported on the possibility of observing the right subclavian artery under normal conditions in the second trimester.…”
Section: View Ix: Subclavian Arteriesmentioning
confidence: 99%